The Comparison of Magpick Anomaly Contours toward Bouguer Anomaly Reduction - Maulidina, Miftakhul; Nadliroh, Kuni; Fauzi, Ah. Sulhan (AI Society & STMIK Indonesia, 2023)
The subsurface structures model can be made by various methods, one of which is the gravity method. The basis of gravity modeling is the difference in density of materials. This can result in gravitational anomalies. Overall gravitational anomalies are known as bouguer anomalies. The gravity anomalies can be separated into local anomalies and regional anomalies. This research was in Mount Kelud, Kediri, Indonesia. The gravity data was processed using Surfer 9 software for the manufacture of two-dimensional contours. After that, researchers performed anomaly separation through MagPick software. In this study, researchers compared the two-dimensional contour results of MagPick gravitational anomalies toward the reduction of bouguer anomalies to regional anomalies. As a result, both show the same accurate contour.